2020
DOI: 10.1002/joe.22060
|View full text |Cite
|
Sign up to set email alerts
|

A case‐based analysis of the competitiveness of the North Indian sugar industry

Abstract: The Indian sugar industry contributes 10% to the country's agricultural GDP, and is a significant part of India's manufacturing base. Although the industry has been the focus of much attention over the years, there remains a lack of case-based studies of its competitiveness. Using data from in-depth interviews with executives in five North Indian sugar companies, we address this gap by applying Porter's theories on competitive advantage, in combination with a technique known as analytic hierarchical process. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Batra and Khan (2005) also analyzed the competitiveness patterns of India and China and found that India has high comparative advantage in labor and resource intensive products including sugar. Besides that, study by Sheetal and Kumar (2016) revealed that Indian sugar exports have strong specialization in all regions.…”
Section: Analysis Of Major Sugar Economiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Batra and Khan (2005) also analyzed the competitiveness patterns of India and China and found that India has high comparative advantage in labor and resource intensive products including sugar. Besides that, study by Sheetal and Kumar (2016) revealed that Indian sugar exports have strong specialization in all regions.…”
Section: Analysis Of Major Sugar Economiesmentioning
confidence: 99%
“…Comparison of trade performances of individual countries in particular commodities is possible with reference of major groups by observing trade patterns (Balassa, 1965). For example, world trade takes several forms like a nation may have advantage in various commodity groups or various trading countries may have competitive advantage in one specific product or commodity (Hillman, 1980;Sheetal and Kumar, 2016). So, it was difficult to know exact specialization level of one commodity at all disaggregated levels.…”
Section: Analysis Of Major Sugar Economiesmentioning
confidence: 99%
“…In present scenario, India and Thailand predominate in raw sugar production (Fairtrade Foundation, 2013) and in case of India, marketing and promotional benefits have been proclaimed by Indian Government to motivate manufacturers to manufacture raw sugar and export the same (CACP, 2014). Integration and diversification in operations have revitalized these sugar economies despite of consistent low sugar prices in past five years (Sheetal and Kumar, 2016b). Resultantly, these nations are found to be very economically viable to manufacture refined (white, brown, cubes and icing) sugar from raw sugar.…”
Section: Marketing Mechanism and Growthmentioning
confidence: 99%
“…Moreover, the Indian sugar industry is highly distorted by the state and central governments and protected across the entire value chain (pricing of sugarcane to the marketing of manufactured sugar) as shown in Table 1 (KPMG, 2007; Sheetal & Kumar, 2016; Vikas B & Babu, 2017). Due to these interferences and exerted controls, the industry is striving to cop up from decadal and financial distress seeing that both net worth and profit margins are turning up negative for majority of the listed public and private sugar companies.…”
Section: Introductionmentioning
confidence: 99%
“…A manager's perception and dynamism about industry structure has the potential to influence various organizational strategies and behaviour (Weerawardena, O'Cass, & Julian, 2006). How do the Industry professionals overlook the Industry's on relevant Porter's five forces model? Indian sugar industry has seen a sea change in sugar marketing; removal of levy quota and abolition of release mechanism in April 2013 (Sheetal & Kumar, 2016; Sheetal & Kumar, 2019; Solomon, 2016). It is interesting to see that current policy regimes, especially partially decontrolling, are affecting the competitiveness of the industry positively or not? Indian sugar industry is politically controlled and regulated at both central and state governments' level (Tondon, 1991; Jyothi, 2014; Vikas B & Babu, 2017).…”
Section: Introductionmentioning
confidence: 99%